2020
DOI: 10.14718/acp.2020.23.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Evidencias de validez factorial de la Escala de desesperanza de Beck en español con muestras clínicas y no clínicas

Abstract: El propósito del presente estudio fue evaluar la estructura interna de la adaptación al español de Escala de Desesperanza de Beck et al. (1974), dada su utilidad y relevancia en la predicción de conductas suicidas. Para esto, se analizaron las respuestas a la escala de 1260 estudiantes universitarios (M = 4.79; DT = 4.29) y de una muestra clínica en la que participaron 150 jóvenes con intento de suicidio de alta letalidad (M = 8.51; DT = 2.38). Se examinó la estructura interna por medio del Análisis factorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Özmen et al (2016) reported that university students in the field of healthcare experienced mild hopelessness. As hopelessness causes the individual to experience anxiety about the future and has a negative effect on mental health (Aloba et al, 2016), hopelessness is usually seen as a depressive disease (Hermosillo-De la Torre et al, 2020). Similar to these previous studies, in this current study, we demonstrated that mental health problems were extremely frequent in the students who were candidates for being a healthcare worker.…”
Section: Discussionsupporting
confidence: 86%
“…Özmen et al (2016) reported that university students in the field of healthcare experienced mild hopelessness. As hopelessness causes the individual to experience anxiety about the future and has a negative effect on mental health (Aloba et al, 2016), hopelessness is usually seen as a depressive disease (Hermosillo-De la Torre et al, 2020). Similar to these previous studies, in this current study, we demonstrated that mental health problems were extremely frequent in the students who were candidates for being a healthcare worker.…”
Section: Discussionsupporting
confidence: 86%
“…A score equal to 9 or higher is an indicator of suicidal behavior. The scale has high reliability (KR = 0.92) [41,42].…”
Section: Beck's Hopelessness Scale Hs-uaa 18mentioning
confidence: 99%
“…However, other researchers found a one- (Kazdin et al, 1983), two- (Kao et al, 2012;Spangenberg et al, 2016;Tanaka et al, 1998) or three-dimension structure for the BHS-20 (Beck et al, 1974;Boduszek & Dhingra, 2016;Dyce, 1996;Kim et al, 2015;Kliem et al, 2018;Kocalevent et al, 2017;Iliceto & Fino, 2015;Steer, Kumar, & Beck, 1993), Szabó et al, 2016). The Spanish versions of the BHS-20 have shown more variation in the dimensional structures, between one and six factors, than those observed in other languages (Aliaga et al, 2006;González, 2009;Hermosillo-De la Torre et al, 2020;Mikulic et al, 2009;Quiñonez-Tapia et al, 2019;Satorres et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…Beck et al (1974) designed a 20-item instrument to quantify the motivational, cognitive, and affective manifestations of hopelessness among adults, the Beck Hopelessness Scale (BHS-20). Worldwide, the dimensionality of the BHS-20 has been studied in different samples, and it has been observed that those items can represent a uni- or multi-dimensional scale with two to six dimensions (Aliaga et al, 2006, 2016; Aloba et al, 2015; Balsamo et al, 2020; Beck et al, 1974; Boduszek & Dhingra, 2016; Dyce, 1996; González, 2009; Hermosillo-De la Torre et al, 2020; Iliceto & Fino, 2015; Innamorati et al, 2014; Kao et al, 2012; Kim et al, 2015; Kliem et al, 2018; Kocalevent et al, 2017; Mikulic et al, 2009; Nissim et al, 2010; Pompili et al, 2007; Quiñonez-Tapia et al, 2019; Rueda-Jaimes et al, 2018; Satorres et al, 2018; Spangenberg et al, 2016; Szabó et al, 2016; Tanaka et al, 2018; Zhang et al, 2015). The differences in the dimensional structure of the BHS-20 are possibly due to the heterogeneity of the populations in which the tool has been tested (Keszei et al, 2010) or methods used to extract the scale’s factors (Lloret-Segura et al, 2014).…”
Section: Introductionmentioning
confidence: 99%